Some analytical aspects of cassava/maize/okra/egusimelon complex mixture: 1. Soli temperature in relation to leaf area variation - Ikeorgu, J.E.G.; Ezumah, H.C. (Elsevier, 1991)
Afternoon soil temperature of about 39°C observed at 5 cm depth under sole cassava (Manihot esculenta Crantz) early in the growing season was reduced by respectively 1.0, 1.3, 3.0 and 4.4°C by intercropping with maize (Zea mays L.), maize/okra (Abelmoschus esculentus Moench), maize/ egusi melon (Citrullus lanatus Thunb.), and maize/okra/egusi melon. There was a negative but significant relationship between soil temperature and combined leaf area index (L) of crops grown in mixture with sparse-canopy cassava (r = -0.91**) and with dense-canopy cassava (r = -0.93**).